Multimodal imaging in Ig G4- related aortitis: case report - Benites-Yshpilco, Lindsay (2024)
We present the case of a 56-year-old patient with fever of unknown origin associated with chest and lumbar pain. Multimodality imaging revealed diffuse peri-aortitis in the thoracic aorta without involvement of the aortic valve, contributing substantially to the diagnosis of Ig G4-associated aortitis. Immunosuppressive therapy was started. Follow-up at five months with cardiac magnetic resonance imaging showed a reduction in the inflammatory process in the thoracic aorta.